2002
DOI: 10.1080/000164802753648178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Electromagnetic Field of Mobile Telephones on Hearing

Abstract: The widespread use of mobile telephones has given rise to concern about the potential influences of electromagnetic fields (EMFs) on human health. Anatomically, the ear is in close proximity to the mobile telephone during use. Hearing loss due to mobile telephone use has not been described in the medical literature; however, if there is a subtle cochlear involvement, it might be detected by means of changes in evoked otoacoustic emissions (OAEs). Thirty volunteers with normal hearing were exposed to mobile tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 16 publications
6
63
0
2
Order By: Relevance
“…Notwithstanding the evidence, Ozturan et al (2002) 11 have recommended caution in mobile phone use to minimize exposure of the auditory system to microwaves. These authors have proposed that mobile phones Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notwithstanding the evidence, Ozturan et al (2002) 11 have recommended caution in mobile phone use to minimize exposure of the auditory system to microwaves. These authors have proposed that mobile phones Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…7,[18][19][20][21]23,24 Various papers have suggested that exposure to mobile phone microwaves has no influence on the activity of cochlear outer hair cells or of cochlear nerve electrical conduction, both in vivo and in vitro. 8,11,15,25,26 Another point is that all of the studies on humans were carried out on normal-hearing volunteers. It is not know whether the cochlea of patients with inner ear conditions would be more sensitive to electromagnetic radiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell phones transmit and receive microwave radiation at frequencies which excite rotation of water molecules and some organic molecules, associated with thermal effects and non-thermal effects. The thermal effects include: headache, sensation of warmth or burning around the ear, burning sensation on the facial skin and alteration of the blood-brain barrier [5].…”
Section: Introductionmentioning
confidence: 99%